A Bibliometrics Analysis of Islamic Economics Literature: 2000-2006 - Harande, Yahya Ibrahim (Universiti Sains Islam Malaysia, 2024)
Presenter from Department of Library and Information Science, Faculty of Education, Bayero University Kano, Nigeria.